Elenberg's Ecological Indicator Values to Predict some Soil Factors in Salaheddinkola Forests of Nowshahr, Iran - Samaneh Tavakoli; Hamid Ejtehadi; Omid Esmailzadeh (تاکسونومی و بیوسیستماتیک, 2019)
One of the most commonly used methods for estimating environmental conditions using plants is the use of Elenberg Indicator values. However, due to objections to the Elenberger system (including caution in its use outside Central Europe), in this study, inaddition to EIVs, three calibration methods (weighted averaging, species response curves by using HOF models, adjusting the original EIVs with respect to a measured gradient using the HOF models) were used to calculate indicator values (IVs) of species in a Hyrcanian forest for two environmental factors (soil reaction or acidity (R) and nitrogen (N)). Also, two bioindication methods WA1 (cover-weighted average) and WA2 (cover-weighted average based on reciprocal squared tolerance values) were used to predict mean R and N values using EIVs, IVs and cover of species for each releve. Then, the regression of the mean values of environmental factors against the measured environmental values in each releve was performed. In general the performance of bioindication methods for soil acidity and nitrogen varied from 1.35- 32.5% and 3.6- 36.7% of the explained variance, respectively. In addition, calibration methods (especially the weighted average method) resulted in better results compared to Elenberg values.